Modelling of JET hybrid plasmas with emphasis on performance of combined ICRF and NBI heating. (5th September 2018) - Gallart, D.; Mantsinen, M.J.; Challis, C.; Frigione, D.; Graves, J.; Belonohy, E.; Casson, F.; Czarnecka, A.; Eriksson, J.; Garcia, J.; Goniche, M.; Hellesen, C.; et al.
Abstract: During the 2015–2016 JET campaigns, many efforts have been devoted to the exploration of high-performance plasma scenarios envisaged for DT operation in JET. In this paper, we review various key recent hybrid discharges and model the combined ICRF+NBI heating. These deuterium discharges with deuterium beams had the ICRF antenna frequency tuned to match the cyclotron frequency of minority H at the centre of the tokamak coinciding with the second harmonic cyclotron resonance of D. The modelling takes into account the synergy between ICRF and NBI heating through the second harmonic cyclotron resonance of D beam ions, allowing us to assess its impact on the neutron rate R NT . For discharges carried out with a fixed ICRF antenna frequency and changing toroidal magnetic field to vary the resonance position, we evaluate the influence of the resonance position on the heating performance and central impurity control. The H concentration is varied between discharges in order to test its role in the heating performance. It is found that discharges with a resonance beyond ̃0.15 m from the magnetic axis R 0 suffer from MHD activity and impurity accumulation in these plasma conditions. According to our modelling, the ICRF enhancement of R NT increases with the ICRF power absorbed by deuterons as the H concentration decreases. We find that in the recent hybrid discharges, this ICRF enhancement varies due to a variation of H concentration and is in the range of 10%–25%. The modelling of a recent record high-performance hybrid discharge shows that ICRF fusion yield enhancement of ̃30% and ̃15% respectively can be achieved in the ramp-up phase and during the main heating phase. We extrapolate the results to DT and find that the best performing hybrid discharges correspond to an equivalent fusion power of ̃7.0 MW in DT. Finally, an optimization analysis of the bulk ion heating for the DT scenario reveals around 15%–20% larger bulk ion heating for the 3 He minority scenario as compared to the H minority scenario.